Interacting in Flow: An Analysis of Rapport-Based Behavior as Optimal Experience. (December 2016) - Nelson, Andrew A.; Grahe, Jon E.; Ramseyer, Fabian
Theorists have long noted the nebulousness of dyadic rapport and its nonverbal correlates. In response to Tickle-Degnen's call for a more theoretically complete analysis of the rapport construct, we empirically evaluated her adaptation of Csíkszentmihályi's optimal experience model with the hope of better conceptualizing rapport's behavioral manifestations. Dyads ( N dyad = 50) engaged in two interdependent tasks and completed a battery of post-task measures gauging their mood and experiences of rapport. To complement self-report measures, we coded rapport-based behavior using both subjective (thin-slice judgments) and objective (Motion Energy Analysis) methodologies. According to Tickle-Degnen's model, dyadic exchanges with moderate levels of expressivity and interpersonal coordination should yield the highest levels of rapport. Although data from our objective coding did not trend in this manner, subjective measurements of coordinated expressivity matched the paradigm's prediction. To our knowledge, this is the first study to empirically support Tickle-Degnen's hypothesis and a novel step toward clarifying the rapport construct.